Approach for fast time–frequency analysis. Issue 4 (1st June 2014) - Cheng, Chun Hing; Pradhan, Pyari Mohan; Mitchell, Joseph Ross
Abstract : S ‐transform (ST) is a time–frequency representation (TFR) that is popularly used in a variety of applications, but prohibitive in both storage and computation for large time series. This study proposes a one‐dimensional fast time–frequency transform (FTFT‐1D) which generates a highly compressed form of the ST directly, without the need to compute the complete ST matrix initially and compress it subsequently. The compression technique used in the FTFT‐1D helps in storage, transmission and visualisation of the ST. The FTFT‐1D encodes the TFR information uniformly and finds the local spectrum instantaneously and accurately. It is useful for real‐time applications such as monitoring, control and filtering. In addition, the FTFT‐1D is memory efficient, robust and adaptive in nature.